Chemoresponsive polymer systems for selective molecular recognition of organic molecules in biological systems. (15th October 2020) - Gosecka, Monika; Gosecki, Mateusz
Abstract: Smart polymer materials that respond to a chemical stimulus are applied for the construction of biomedical devices and purification/separation systems. Small organic molecules are a particular type of stimulus. Their abnormal concentration indisputably indicates certain diseases. They are also hazardous environment contaminants. Polymer materials, which structure is selectively changed in the presence of a defined organic compound are promising in view of regulation of certain biomedical functions, as well as in view of chemical detectors construction. This review summarizes the state of the art in the self-assemblies of amphiphilic copolymers and polymer networks sensitive toward organic species, with an emphasis on the reports from the last decade. We focus on the relationship between the selectivity of introduced receptor moieties responsible for the change of material structure, the overall structure of material and its functionality. Graphical abstract: Image, graphical abstract